The Role of Parents in Responding to Bullying Actions at the Elementary School Level - Ashabul Fadhli; Recy Harviani Zurwanty; Syelfia Dewimarni (Ta'dib, 2024)
This study aims to determine the role of parents in Agam Regency in preventing bullying against children in elementary schools. Juridically, the state regulates that parents are obliged to maintain, educate, and instill good ethical values to children. On that basis, each parent is obliged to carry out their respective roles to develop children's potential so that children avoid bullying in elementary schools. This research departs from field research with descriptive research type. The subjects of this study were parents of elementary school students in Agam Regency as many as 79 respondents consisting of 60 women (mothers) and 19 men (fathers). The research instrument is a valid questionnaire on the role of parents in responding to bullying. The data obtained were analyzed using the percentage technique. The results of this study reveal that fathers and mothers have played a good role in encouraging the development of children's potential positively. Likewise with the item of equipping children with self-concept strengthening. Meanwhile, the item about parents' actions to provide time with children has not produced good percentage criteria. The wrong perspective of parents in carrying out their roles has implications for the non-optimal guidance, education, and guidance to children in terms of preventing bullying in elementary schools.